Trade, Wage Gaps, and Specific Human Capital Accumulation - Ngo Van Long; Raymond Riezman; Antoine Soubeyran (Center for Economic Studies and ifo Institute (CESifo), 2003)
We develop a new framework for the analysis of the impact of trade liberalization on the wage structure. Our model focuses on the decision of workers to accumulate firm-specific skills, by on-the-job training, knowing that this means their future wages will have to be negotiated, and that the outcome of negotiation will depend on the profitability prospect of firms operating in a new trading environment. We show that trade liberalization may reduce the welfare of a developing country because of its adverse effect on skill accumulation. We also explore the effects of trade liberalization on the wage gap between skilled and unskilled workers.
Keywords: 330; wage gap; human capital; trade liberalization